Development of physical and functional abilities of students of the special medical group (Bangladesh Journal of Medical Science, 2025)
The aim of the study Is to improve the level of development of functional abilities and physical qualities of students with health limitations.Methods The pedagogical experiment was conducted in 2023 at Moscow University in Russia. The study involved 128 students aged 18-19 who have health limitations. Adaptive physical education classes were held twice a week for 90 minutes. 64 students from the control group studied according to the adaptive physical education program at a higher educational institution. 64 students from the experimental group studied according to the developed experimental program aimed at improving functions of the respiratory system and developing physical qualities.Results After the end of the educational experiment, the indicators in the control group improved in the Stange Test by 2.6% (p>0.05), the Genchi Test remained at the same level of 35±1 sec. The long jump increased by 0.5% (p>0.05), and the arm muscle strength improved by 4.5% (p>0.05). The indicators of the flexibility test decreased by 7.7% (p>0.05), and abdominal muscle strength decreased by 5% (p>0.05). These results show the low efficiency of the standard adaptive physical education program at university. In the experimental group, the average indicators in the Stange Test became higher by 5% (p>0.05), and in the Genchi Test by 12.5% (p0.05), but the abdominal muscle strength increased by 21.6% (p0.05), and flexibility improved by 33.3% (p